Réponses

2013-02-03T17:52:53+01:00

NB(xB-xN; yB-yN)   NC(xC-xN; yC-yN)  NA(xA-xN; yA-yN)

 

         X NB-XNC=XNA                                  YNB-YNC=YNA

<=> xB-xN - [xC-xN]=xA-xN               <=> yB-yN - [yC-yN]=yA-yN

<=> -4-xN-7+xN= 2-xN                     <=> 3-yN-5+xN = -1-yN

<=> -11=2-xN                                    <=> -2=-1-yN

<=> -13=-xN                                      <=>-1=-yN

<=> xN=13                                         <=> yN= 1

      

 

                                               Soit N(13;1)